The XMM-Newton Line Emission Analysis Program (X-LEAP). I. Emission-line Survey of O vii, O viii, and Fe L-shell Transitions - Zeyang Pan; Zhijie Qu; Joel N. Bregman; Jifeng Liu (The Astrophysical Journal Supplement Series, 2024)
The XMM-Newton Line Emission Analysis Program (X-LEAP) is designed to study diffuse X-ray emissions from the Milky Way (MW) hot gas, as well as emissions from the foreground solar wind charge exchange (SWCX). This paper presents an all-sky survey of spectral feature intensities corresponding to the O vii , O viii , and iron L-shell (Fe-L) emissions. These intensities are derived from 5418 selected XMM-Newton observations with long exposure times and minimal contamination from point or extended sources. For 90% of the measured intensities, the values are within ≈2–18 photons cm ^−2 s ^−1 sr ^−1 (line unit (LU)), ≈0–8 LU, and ≈0–9 LU, respectively. We report long-term variations in O vii and O viii intensities over 22 yr, closely correlating with the solar cycle and attributed to SWCX emissions. These variations contribute ∼30% and ∼20% to the observed intensities on average and peak at ≈4 and ≈1 LU during solar maxima. We also find evidence of short-term and spatial variations in SWCX, indicating the need for a more refined SWCX model in future studies. In addition, we present SWCX- and absorption-corrected all-sky maps for a better view of the MW hot gas emission. These maps show a gradual decrease in oxygen intensity moving away from the Galactic center and a concentration of Fe-L intensity in the Galactic bubbles and disk.